ASPEK SOSIO-BUDAYA, KEBIJAKAN PEMERINTAH, DAN MENTALITAS YANG BERPENGARUH TERHADAP INTEGRASI SOSIAL DALAM MASYARAKAT SUMATERA BARAT - Eriyanti, Fitri (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2013)
This study aims to explore the socio-cultural aspects, policies, and the mentality that influence social integration in the western Sumatran society. Location of this study spread over counties and cities in West Sumatra, represented by the six District/City, namely: Pasaman Barat, Solok, Pesisir Selatan, Sawahlunto, Dharmasraya, and Bukittinggi. Selection of sample areas is based on the degree of heterogeneity of society. The study was designed in the form of a survey with a qualitative approach. Data collected through interviews and documentation studies. Data were analyzed in stages through data collection (recording), categorizing the data, coding the data by category, and data interpretation. The results obtained from this research is presented in a description of the socio-cultural community which is reflected in the socio-cultural